Hyperreality of School Graduation in Visual Culture: An Analysis of the Toga Video from SMK Citra Bangsa Mandiri on Instagram - Ahmad Syadzali; Muhammad Syafi'i; Gladys Adieba (Metacommunication: Journal of Communication Studies, 2026)
This study examines how the graduation process at SMK Citra Bangsa Mandiri Purwokerto is represented through video uploads on social media, and how such visualizations construct a new meaning of graduation. The main issue addressed is the shift in the meaning of graduation when academic symbols typically used at the university level are applied in the context of secondary schools. To address this issue, the study employs a qualitative visual analysis approach of the videos’ aesthetic elements, such as composition, lighting, camera angles, and presentation structure, which are then combined with an interpretation of social meanings derived from public responses. The results show that the dominance of academic symbols, cinematic visual aesthetics, and structured event packaging create a graduation representation that resembles a university commencement, thereby generating a new reality accepted by the audience without questioning the vocational context of the school. These findings highlight the capability of social media to influence how educational institutions present themselves and how the public assigns meaning to educational symbols. The study concludes that in the digital era, graduation is no longer merely an academic ritual but has become a visual construction that follows the logic of attention and social media aesthetics.